Concept of Sangyaharana (Anaesthesia) and Pain Management in Ayurveda: A Critical Review: LifeScience-Surgery - Sharma, Dr. Shivam; Asutkar, Dr. Sheetal (International Journal of Life Science and Pharma Research, 2023)
Despite highly developed scientific studies, pain continues to be the leading cause of disability that affects a sizable portion of theglobal population. An integrated approach to pain management may alleviate the distress associated with treating this symptom, which can bepresent in various degrees. The Sushruta Samhita is the only complete work that addresses the difficulties of actual surgery and midwifery.Sushruta was a deeply skilled surgeon. Since the beginning, doctors have recognized the importance of anesthesia and have worked to createthis pain-free surgical environment. Sushruta utilized Sangyaharana for painless surgery. The Sushruta Samhita is where we first see asystematic approach to organizing the surgical expertise of more experienced surgeons. Some dravyas, such as Madya (wine), have beendescribed by Sushruta, while mohachurna has been discussed in Bhojaprabandha. According to Charaka, the tikshna sura should beadministered to the patient before surgery. Some study experts have also detailed the use of Ayurvedic medications, including Vacha,Ashwagandha, Bramhi, Parijata, and Parasika yavani, postoperatively to reduce pain, edema, and anxiety in patients.A major herbal anestheticis still needed, though. This review provides a historical overview of the Sangyaharana (Anaesthesia) practiced by ancient surgeons. Thisarticle highlights the concept of sangyaharana (anesthesia) and pain management in Ayurveda. The main objective of this article was to collectdata from different articles and textual concepts and present it systematically. This review article covers a combination of all the drugs andayurvedic herbal methods for sangyaharana and pain management. Most previous articles had very little information about the drugs andmethods of sangyaharn, and the data was very discrete and in random order. This article covers all the details in a systematic and orderlymanner. This article provides information regarding various Ayurvedic treatment modalities for pain management. It also shows the need foran effective Ayurvedic anesthetic drug having sangyaharan properties in the present era, and scientists and researchers have to work on thison a priority basis. The article concludes with how the sangyaharna was given in old times and old literature about sangyaharna and drugs thathelp pain management in pre-sangyaharna and their work in the modern era.